An investigation of red blood cell concentrate quality during storage in paediatric‐sized polyvinylchloride bags plasticized with alternatives to di‐2‐ethylhexyl phthalate (DEHP). Issue 3 (8th December 2015) - Serrano, K.; Levin, E.; Chen, D.; Hansen, A.; Turner, T. R.; Kurach, J.; Reidel, A.; Boecker, W. F.; Acker, J. P.; Devine, D. V.
Abstract : Background and Objectives: Di‐2‐ethylhexyl phthalate (DEHP) is a blood bag plasticizer. It is also a toxin, raising concerns for vulnerable populations, for example, neonates and infants. Here, the in vitro quality of red cell concentrates (RCC) stored in paediatric bags formulated with alternative plasticizers to DEHP was compared. Materials and Methods: RCC were pooled and split into polyvinylchloride (PVC)/DEHP, PVC/1, 2‐cyclohexanedicarboxylic acid diisononyl ester (DINCH) or PVC/butyryl trihexyl citrate (BTHC) bags. Quality was assessed on storage days 5, 21, 35 and 43. Results: Metabolism differed among the bags: pCO2 levels were lowest and pO2 were highest in BTHC bags. Glucose consumption and lactate production suggested higher metabolic rates in BTHC bags. ATP levels were best maintained in DINCH bags (day 43 mean level: 2·86 ± 0·29 μmol/g Hb). RCC in BTHC bags had the greatest potassium release (54·6 ± 3·0 mm on day 43). From day 21, haemolysis was higher in BTHC bags ( P < 0·01) and by day 43 had exceeded 0·8% (0·85 ± 0·10%). RCC in BTHC bags showed more microparticle formation than RCC in DEHP or DINCH bags. Conclusion: The results suggest that the BTHC formulation used was detrimental to RBC quality. DINCH bags could be a viable alternative to DEHP: they outperformed DEHP bags energetically, with better maintenance of ATP levels.